2020
DOI: 10.13057/biodiv/d210717
|View full text |Cite
|
Sign up to set email alerts
|

Screening for probiotic of lactic acid bacteria isolated from the digestive tract of a native Aceh duck (Anas platyrhynchos)

Abstract: Abstract. Risna YK, Harimurti S, Wihandoyo, Widodo. 2020. Screening for Probiotic of lactic acid bacteria isolated from the digestive tract of a native Aceh duck (Anas platyrhynchos). Biodiversitas 21: 3001-3007. The lactic acid bacteria (LAB) isolated from the digestive tract of a native Aceh duck has emerged as a potential probiotic supplement for duck feed. In this study, we isolated the LAB from the digestive tract of an Aceh duck (Anas platyrhynchos) and identified the species and bacterial characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…According to Risna et al (2022) lag phase is where the bacteria still adjust to the new environment, so the growth is slow and the metabolic process has not been maximized. In addition, the process of making peanut chocolate jam did not involve the incubation process so that the bacteria did not have enough time to produce a metabolic product optimally.…”
Section: Ph Valuementioning
confidence: 99%
“…According to Risna et al (2022) lag phase is where the bacteria still adjust to the new environment, so the growth is slow and the metabolic process has not been maximized. In addition, the process of making peanut chocolate jam did not involve the incubation process so that the bacteria did not have enough time to produce a metabolic product optimally.…”
Section: Ph Valuementioning
confidence: 99%
“…The previous studies have reported that LAB can be obtained from the GIT of duck. LABs were isolated from the small intestine [20,21], cecum, and colon of Muscovy ducks [22] or from the crop until the cecum of Aceh ducks [23]. Ducks can survive in various agroclimatic conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria has the ability to secrete antibacterial substances such as lactic acid, bacteriocin, and active peptides that could inhibit the growth of pathogenic bacteria, and metabolite substances with antioxidant activities such as butyrate and folate [6,7]. Antioxidants produced by the probiotics are useful to reduce free radicals that causes oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%